SAA restricts T cell mediated anti-tumor immunity by limiting antigen presentation in lung cancer - Huang, Mei; Shi, Run; Xu, Cong; Zhang, Yihan; Du, Xiaoyue; Wen, Shaodi; Wang, Chunbin; Jiang, Feng; Zhou, Guoren; Wang, Xin; Shen, Bo (Frontiers in Immunology, 2025)
BackgroundSerum amyloid A (SAA), an acute-phase pro-inflammatory protein, is overexpressed in several cancers and is involved in shaping pro-tumor responses. We have previously reported that lung cancer stem cells secrete SAA, which contributes to tumor progression by inhibition of TH1 immunity. Here, we extended our studies to examine the mechanism of SAA mediated immunosuppression in both antigen-presenting cells (APCs) and the subsequent activation of T cells.Methods & resultsUsing ex vivo co-culture systems and in vivo mice models, we found that SAA impaired dendritic cell and macrophage activation and drove macrophages toward an M2 phenotype with reduced antigen presentation. Lung cancer cells overexpressing SAA also consistently showed impaired CD8+ T cell infiltration and cytotoxicity, while SAA neutralization were efficient at enhancing CD8+ T cell activation and response to anti-tumor immunity. Mechanistically, we found that the immunosuppressive phenotype induced by SAA on APCs is mediated in part by CD36. Critically, inhibiting SAA by neutralization antibody recovered APC activity and enhanced T cell-dependent tumor control.Conclusionour results identify SAA as an important immunosuppressive mediator in the tumor microenvironment, implying that the SAA neutralizing antibody may be a potential target for the improvement of lung cancer immunotherapy.